Agricultural innovation system capacity development: Tools, principles or policies? - Hall, A.; Sulaiman, R.; Beshah, T.; Madzudzo, E.; Puskur, Ranjitha (2009)
One of the most notable changes in the field of agricultural development has been the growing popularity of thinking in terms of innovation systems rather than just focusing on research. Addressing the scarcity of fodder: livestock in northern Nigeria. A persistent criticism of agricultural research, voiced by a whole generation of rural development practitioners and system thinkers, has been the unresponsiveness of research to the changing needs of clients. It has also been observed that while research is good at developing new technologies, the adoption of these technologies has been weak. Focusing on innovation rather than research shifts the emphasis to the application of knowledge and technology rather than just their production. Although there seems to be growing acceptance of this logic in the development research community, what seems to be less clear is how the idea of an innovation system can be translated into practice. The challenge in this is the highly context-specific nature of capacities that need to be developed. Researchers are now exploring a number of ways to nurture the development of these context-specific capacities.